a PENGARUH PENDAPATAN, AKSES PELAYANAN KESEHATAN DAN AKSES INFORMASI KESEHATAN TERHADAP LITERASI KESEHATAN WANITA USIA SUBUR DI PUSKESMAS WIROBRAJAN KOTA YOGYAKARTA - wahyuningsih, tutik (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2022)
Background: Health literacy is a term used to describe the degree of a person's ability to obtain, assess, understand health information and services to make appropriate health decisions. The results of the research survey conducted on 10 respondents using an NVS (New Vital Sign) questionnaire from 6 questions regarding an ice cream label, 9 out of 10 respondents had several levels of health literacy with a very low score of 1-2. Objective: This study aims to determine the level of health literacy and the factors that influence the health literacy of women of childbearing age at the Wirobrajan Public Health Center, Yogyakarta City. Methods: This type of research uses descriptive quantitative research with a one-time research design (Cross sectional). Collecting data by giving a questionnaire. Results: The results showed that from 137 respondents there were 56% of respondents who had low health literacy and 44% of respondents had high health literacy. There is an effect of access to health services on health literacy p=0.041 <0.05. There is an effect of income on health literacy p=0.001 <0.05. And there is an effect of access to health information on health literacy p= 0.000 < 0.05. Conclusion: There is an effect of access to health services on health literacy, there is an effect of income on health literacy and there is an effect of access to health information on health literacy